Investigation of Bearingless Partitioned-Stator Flux-Switching Permanent-Magnet Slice Motors - Madanzadeh, Sadjad; Gruber, Wolfgang; Mallinger, Stefan; Jastrzebski, Rafal P.; Nevaranta, Niko (Institute of Electrical and Electronics Engineers (IEEE), 2026)
Flux-switching permanent-magnet machines have gained popularity because their distinctive design places both the permanent magnets and the windings in the stator. This configuration not only improves the structural integrity of the rotor under centrifugal stresses but also makes cooling of the stationary permanent magnets easier and more efficient compared to rotor permanent-magnet structures. These machines are highly versatile and well-suited for applications requiring bearingless motors, including cleanrooms, medical equipment, and pharmaceutical production. However, because the magnetic core must accommodate both the windings and the permanent magnets, it experiences saturation, resulting in performance constraints. This paper proposes a novel bearingless partitioned-stator flux-switching permanent-magnet slice motor architecture. To support this concept, the study focuses on unaddressed challenges in the electromagnetic design of bearingless slice motors, particularly those related to core saturation and the optimization of torque and force performance. By separating the stator into sections containing permanent magnets and copper, iron core saturation is mitigated, resulting in improved torque density. Machine performance is further improved through winding optimization, where various winding schemes are evaluated. The proposed design and underlying principles are validated using 2D and 3D finiteelement analyses of the optimized configurations. Experimental validation confirms the theoretical findings, providing a thorough understanding of the operational characteristics of the motor.